USE OF MOLECULAR MARKERS IN WHEAT BREEDING AT THE KRASNODAR LUKYANENKO RESEARCH INSTITUTE OF AGRICULTURE - L. A. Bespalova; A. V. Vasilyev; I. B. Ablova; V. A. Filobok; Zh. N. Khudokormova; R. O. Davoyan; E. R. Davoyan; G. I. Karlov; A. A. Soloviev; M. G. Divashuk; N. K. Mayer; M. V. Dudnikov; et al. (Вавиловский журнал генетики и селекции, 2014)
Pilot experiments on molecular marker application in breeding of winter wheat at the Krasnodar Lukyanenko Research Institute of Agriculture (KNIISH) are described. The most efficient ways of marker application in creating new cultivars are outlined. A variety of genes responsible for valuable agronomic traits in KNIISH varieties have been detected.